Hubungan kualiti penyeliaan pengajaran dan pembelajaran di bilik darjah dengan efikasi guru (The relationship between quality teaching and learning supervision with teachers' efficacy) - Mohd Yusoff, Nurahimah; Osman, Rafisah (Universiti Sains Malaysia Press, 2010)
This paper discusses the relationship between quality teaching and learning supervision with teachers’ efficacy.In the context of the study, quality supervision requires knowledge, interpersonal skills and technical skills.Previous studies have shown that knowledge, interpersonal skills, and technical skills have significant relationships with teachers’ efficacy.Therefore, a correlation study was carried out to explore the relationship between the variables.The finding from 856 secondary school teachers’ indicated that there was a significant relationship between quality supervision and teachers’ efficacy.In conclusion, quality supervision can increase or decrease teachers’ efficacy.